Non-halal ingredients in products with special reference to toothpaste looking at the Malaysian law / Nurdalina Md. Yassin and Christy Eleanor Anak Dublin - Md. Yassin, Nurdalina; Dublin, Christy Eleanor (2006)
This project paper is about the issue of non-halal ingredients in products in Malaysia with special reference to toothpaste by looking at several related laws such as Trade Descriptions Act 1972, Consumer Protection Act 1999 etc. Why we choose this topic is because there have been many rumours about one of the toothpaste brand which contains non-halal ingredients. In this project paper, it touches about the duties and responsibilities of manufacturers towards the consumers, the consumer's rights, JAKIM's power and authority and also focusing on issues relating to toothpaste. It is also included in this project paper, the definition of "halal' and "haram" from the Islamic point of view and the civil law point of view. A survey has also been conducted by distributing questionnaires to 50 respondents which include students, housewives and working persons to get ideas from the consumers about their thoughts and opinion on "halalharam" issues and the toothpaste issue.